The Use of DNA Microsatellite Markers for Genetic Diversity Identification of Soybean (Glycine max (L) Meriil.) as a Supplementary Method in Reference Collections Management - Nina Agusti Widaningsih; Edi Purwanto; N. Nandariyah; R. Reflinur (Indonesian Journal of Biotechnology, 2014)
Large number of new soybean varieties are mostly derived from crosses of elite genotypes resulted ina narrowing of both the genetic diversity and the phylogenetic relationship between soybean varieties. Thus,discrimination among soybean varieties is becoming more diffi cult, especially when morphological traits wereapplied. In Plant Variety Protection (PVP) system, new varieties of soybeans including granted PVP right, localand breeding varieties registered in PVP offi ce were frequently increased, implicate on increasingly the numberof soybean varieties collections. To assist the management of varieties collections, a standard fi ngerprinting datais further needed. In comparison to the management of plant collection in the fi eld, molecular marker systemswhich are rapid, reliable, informative and relatively simple are continually sought for practical applications ingermplasm conservation, management and enhancement. This study aimed to identify the genetic diversity andphylogenetic relationship of soybean varieties that have earned PVP Right as well as local varieties and breedingvarieties registered in the PVP offi ce using microsatellite or simple sequence repeats (SSR) markers.This study was conducted in Molecular Biology laboratory, Indonesian Center for Agricultural Biotechnologyand Genetic Resources Research and Development (ICABIOGRAD) Bogor, from February to May 2013. The datawere analyzed using the genetic analysis package NTSYSpc 2.02i and PowerMarker V3.25. The result showed arelatively narrow genetic diversity among 45 varieties of soybean analyzed in present study which were indicatedby the small number of genotypes and total number of alleles (NA), and the low value of gene diversity and PICvalues (<0.75). Cluster analysis showed that the grouping varieties are not related to morphological characters butrelated to phylogeny relationship between varieties. Despite the group of varieties were not clustered in accordancewith morphological characteristics, SSR marker can be a powerful tool for discriminating varieties, so that it couldbe useful for initial varieties identity in conjunction with genetic diversity analysis.